La falta de estimulación temprana y su incidencia en el desarrollo de la motricidad gruesa de los niños de 3 y 4 años que asisten al centro de desarrollo integral Estrellitas de Luz de la ciudad de Loja. Período julio – noviembre del 2009. Lineamientos propositivos. Terapia psicomotriz - Paladines Bernal, Sandra Mercedes (2014)
This thesis entitled: "THE LACK OF EARLY STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF GROSS MOTOR SKILLS OF CHILDREN 3 AND 4 YEARS ATTENDING THE CENTRO DE DESARROLLO INTEGRAL ESTRELLITAS DE LUZ CITY OF LOJA. PERIOD JULY - NOVEMBER 2009 GUIDELINES PROACTIVE. PSYCHOMOTOR THERAPY "is structured and developed according to regulations graduation National University of Loja. The general objective that guided the research was: To determine the influence of the lack of early stimulation in the development of gross motor skills of children 3 and 4 years old who attend the CENTRO DE DESARROLLO INTEGRAL ESTRELLITAS DE LUZ. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive and Statistical Model; techniques used were: A Survey aimed at teachers and parents of children 3-4 years attending the Child CENTRO DE DESARROLLO INTEGRAL ESTRELLITAS DE LUZ city of Loja, in addition to managing an observation guide to establish implementation of early learning activities, to assess the gross Motor. 29.4% of teachers engaged in moving for children / as, 23.5% do balance exercises, jumping 17.6% children, 17% down stairs and finally up 11.8% stairs. Valued Development Gross Motor of children from 3-4 years of age attending CENTRO DE DESARROLLO INTEGRAL ESTRELLITAS DE LUZ, the following results were obtained: as many aspects are on the scale of good, a smaller percentage with difficulty, and a small percentage fine, the scale is not minimized. It follows that the major problems lie in aspects of scale, "only with difficulty", therefore will face therapy helps these aspects, they are:. Walking, balance, rhythm, jump, climb, climb , movement coordination, body awareness.